2001
DOI: 10.1046/j.1469-0705.2001.00221.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of acupuncture on Doppler ultrasound in pregnant women

Abstract: Our study indicates a positive influence of acupuncture treatment on umbilical artery waveforms when using a combination of SP-6 (Sanyinjiao) and LI-4 (Hegu) acupuncture points. Acupuncture performed at these sites either individually or in combination does not seem to affect blood flow in the fetal aorta or uterine artery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 19 publications
(16 reference statements)
1
9
0
3
Order By: Relevance
“…The three trials of acupuncture increased the baseline blood perfusion up to 2.5-fold in the female; there was no significant difference in baseline perfusion in the male subject. The acute and chronic effects of acupuncture are in good concordance with the previous studies using other conventional methods 2,11,12. These results might indicate the beneficial effect of acupuncture on peripheral vascular function.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The three trials of acupuncture increased the baseline blood perfusion up to 2.5-fold in the female; there was no significant difference in baseline perfusion in the male subject. The acute and chronic effects of acupuncture are in good concordance with the previous studies using other conventional methods 2,11,12. These results might indicate the beneficial effect of acupuncture on peripheral vascular function.…”
Section: Resultssupporting
confidence: 89%
“…It increases blood perfusion 2. Also, there was a positive influence of acupuncture treatment in pregnant women when using a combination of SP-6 (Sanyinjiao) and LI-4 (Hegu) acupuncture points 11. Houxi (SI-3) is believed to soothe hand numbness (Figure 1A).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Zeisler et al demonstrated a positive infl uence of acupuncture treatment on the umbilical artery waveforms when used in combination with Sanyinjiao (SP6) and Hegu (Li6) acupoints. 16 Yinlingquan (SP9) was also added because it has been demonstrated to relieve pain of the knee.…”
Section: Acupoint Selection Analysismentioning
confidence: 99%
“…Zeisler et al [33] belegten ebenfalls signifikante Effekte der Akupunktur auf die Durchblutung der A. umbilicalis sowie auf die fetale Herzfrequenz.…”
Section: Akupunktur In Der Schwangerschaftunclassified